(untitled) (Vietnam Journal of Community Medicine, 2025)
Objective: To evaluate the clinical outcomes of microsurgical repair for ulnar nerve lacerations in the distal third of the forearm during emergency conditions and to identify factors influencing functional recovery. Methods: A cross-sectional, prospective study of 39 patients aged 18-60 with complete ulnar nerve transection in the distal forearm. All underwent microsurgical neurorrhaphy within 7 days. Outcomes were assessed after ≥ 6 months using the BMRC scale. Results: 82.1% of patients achieved good to very good functional recovery. Age (p < 0.05) and supervised rehabilitation (p < 0.05) were significantly associated with outcomes. No significant difference was observed between surgeries performed < 24 hours and 24 hours to 7 days after injury. Conclusion: Emergency microsurgical repair of ulnar nerve injuries in the forearm yields favorable outcomes, particularly when combined with supervised physiotherapy. The findings provide practical guidance for treating peripheral nerve injuries in both specialized and general medical settings.